Pulmonary hypertension and home-based (PHAHB) exercise intervention: protocol for a feasibility study. Issue 5 (10th May 2021) - McCormack, Ciara; Kehoe, Brona; Hardcastle, Sarah J; McCaffrey, Noel; McCarren, Andrew; Gaine, Sean; McCullagh, Brian; Moyna, Niall
Abstract : Introduction: Novel therapies for pulmonary hypertension (PH) have improved survival and slowed disease progression. However, patients still present with symptoms of exertional dyspnoea and fatigue, which impacts their ability to perform activities of daily living, reduces exercise tolerance and impairs their quality of life (QoL). Exercise training has shown to be safe and effective at enhancing QoL and physical function in PH patients, yet it remains an underused adjunct therapy. Most exercise training for PH patients has been offered through hospital-based programmes. Home-based exercise programmes provide an alternative model that has the potential to increase the availability and accessibility of exercise training as an adjunct therapy in PH. The purpose of this study is to investigate the feasibility, acceptability, utility and safety of a novel remotely supervised home-based PH exercise programme. Methods: Single arm intervention with a pre/post comparisons design and a follow-up maintenance phase will be employed. Eligible participants (n=25) will be recruited from the Mater Misericordiae University Hospital PH Unit. Participants will undergo a 10-week home-based exercise programme, with induction training, support materials, telecommunication support and health coaching sessions followed by a 10-week maintenance phase. The primary outcomes are feasibility, acceptability, utility and safety of the intervention. Secondary outcomes will include the impact of the intervention on exercise capacity, physical activity, strength, health-related QoL and exercise self-efficacy. Ethics and dissemination: Ethics approval has been obtained from the Mater Misericordiae Institutional Review Board REF:1/378/2032 and Dublin City University Research Ethics DCUREC/2018/246. A manuscript of the results will be submitted to a peer-reviewed journal and results will be presented at conferences, community and consumer forums and hospital research conferences. Trial registration number: ISRCTN83783446 ; Pre-results.